MANAGEMENT OF LABOR MOTIVATION ON ENTERPRISES OF SANATORIUM-RESORT COMPLEX - Mitsenko, Mitsenko; Riznyk, Riznyk (Індустрія туризму і гостинності в Центральній та Східній Європі, 2021)
The features are identified and the problematic aspects of labor motivation in the enterprises of the sanatorium and resort complex are singled out. It is emphasized that macroeconomic environment of enterprises is ambiguous, characterized by both positive aspects and signs of a systemic crisis, which affects the formation of prerequisites for their personnel management and labor motivation. It is stressed that there are disproportions in the regional markets for sanatorium and health services. The factors of the internal environment, which act as motivating mechanisms, are revealed. It is concluded that further development of the enterprises of the industry is largely determined by both qualitative personnel provision and the efficiency of personnel work and is directly related to the proper work motivation. The key subjects of motivation are specified, the conceptual principles of labor motivation management at enterprises of the sanatorium-resort complex are improved, for which the characteristics of motivation are supplemented. The attention is paid to the peculiarities of the labor motivation of certain categories of enterprise employees of the sanatorium and resort complex and the need for a targeted approach to the management of the their work motivation. Strategic approaches to motivating work of certain categories of personnel are recommended. The conceptual characteristics of the modern system of enterprises motivation management of the sanatorium and resort complex are singled out. An algorithm for the implementation of this system is proposed for adaptation of the system of work motivation management to business processes.